Electrochemical evaluation of stainless steel welded tubes - Rodríguez-Yáñez, Javier E. (2014)
The recovery of 316L steel capillaries used in neutral geothermal wells orbital welding by weld is evaluated from the point of view of its resistance to corrosion in the conditions of use, through basic electrochemical techniques. In the pre-treatment is more convenient than carrying out a chemical pickling prior to welding for 5 minutes. While subsequent to the application of welding heat treatment of stress reduction is not justified from the standpoint of corrosion resistance. There is also the comparison of capillaries capillary soldiers regarding new and used soldier’s capillaries having an intermediate behavior between the two.